2017
DOI: 10.1016/j.nme.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium retention and thermal conductivity in ion-beam displacement-damaged tungsten

Abstract: Retention of plasma-implanted D is studied in W targets damaged by a Cu ion beam at up to 0.2 dpa with sample temperatures between 300 K and 1200 K. At a D plasma ion fluence of 10 24 /m 2 on samples damaged to 0.2 dpa at 300 K, the retained D retention inventory is 4.6x10 20 D/m 2 , about ~5.5 times higher than in undamaged samples. The retained inventory drops to 9x10 19 D/m 2 for samples damaged to 0.2 dpa at 1000 K, consistent with onset of vacancy annealing at a rate sufficient to overcome the elevated ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Tynan et al . also indicated that pre-damaged tungsten increased deuterium retention 29 . Since the dislocations cannot reduce the hydrogen embrittlement in iron, the formation of voids during ion irradiation is a key point to improve the hydrogen embrittlement in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…Tynan et al . also indicated that pre-damaged tungsten increased deuterium retention 29 . Since the dislocations cannot reduce the hydrogen embrittlement in iron, the formation of voids during ion irradiation is a key point to improve the hydrogen embrittlement in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…Fu 4,a It is thought that this is caused by the so-called barrier effect in which the implanted He ions form a thin (few tens of nm) He nanobubble layer in the sample and act to reduce the D retention either via the formation of interconnected pathways to the sample surface, leading the D ions to diffuse back to the plasma and resulting in the D retention decreasing, or by the formation of a diffusion barrier to the D atoms, or both [6]. On the other hand, many studies [7][8][9][10][11] have shown that radiation damage in W induced e.g. using energetic heavy ions such as Cu and W or by intense neutron irradiation, followed by D 2 plasma exposure, results in a substantial increase in D retention relative to the retention in undamaged W. This is usually attributed to the fact that radiation damage induces new defects such as vacancies and dislocations, which supply additional traps for the diffusion D ions, resulting in the total D retention increasing.…”
Section: Nuclear Fusionmentioning
confidence: 99%
“…TEM observations with similar proton irradiated materials showed increasing defect density with DPA up to a saturation limit around 0.2 DPA in tungsten from where on mostly the loop defect size increased with constant loop density [5]. Also [6] found saturation effects in the 0.2 DPA region with a factor 5.5 increase in retention at 300 K, but by using heavy ions with 1 μm damage range. Protons with ∼15 μm range showed a significantly higher factor of ∼13 increase for D retention in W [4].…”
Section: Introductionmentioning
confidence: 81%